Pyrrocidines A and B demonstrate synergistic inhibition of Fusarium verticillioides growth - Lofton, Lily W.; Read, Quentin D.; Hamilton, Hailey L.; Glenn, Anthony E.; Hawkins, Jaci A.; Mitchell, Trevor R.; Gold, Scott E. (Frontiers in Microbiology, 2025)
Fusarium verticillioides—a mycotoxigenic fungus and food safety threat—coinhabits maize kernels with Sarocladium zeae. This protective endophyte produces secondary metabolites of interest, pyrrocidines A and B, which inhibit the growth of F. verticillioides and specifically block fumonisin biosynthesis. Previous transcriptomic analyses found FvZBD1 (FVEG_00314), a gene adjacent to the fumonisin biosynthetic gene cluster, to be induced over 4,000-fold in response to pyrrocidine challenge. Deletion of FvZBD1 resulted in dramatic increases in fumonisin production (FB1 >30-fold). Here, using pyrrocidine dose-response assays, we discovered a potent synergy between pyrrocidines A and B, where they functioned powerfully together to inhibit F. verticillioides growth. Further, results provided evidence that FvZBD1 confers partial tolerance to pyrrocidines, particularly pyrrocidine A, and that pyrrocidine functions through FvZBD1 to effectively eliminate fumonisin biosynthesis. Additionally, we showed that the FvABC3 (FVEG_11089) mutant, earlier described as hypersensitive to pyrrocidine, is particularly sensitive to pyrrocidine B. Thus, pyrrocidine A and B show different target specificity (FvZBD1 or FvABC3) and synergistic action. These findings will help inform the optimization of maximally efficacious S. zeae strains for eliminating F. verticillioides colonization and fumonisin contamination in maize cropping systems. This novel study contributes significantly to our knowledge of competitive microorganism relationships and the role of secondary metabolites in antagonistic fungal-fungal interactions.